2007
DOI: 10.1111/j.1365-2982.2007.00995.x
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal electrical stimulation improves delayed gastric emptying and vomiting induced by duodenal distension in dogs

Abstract: The aim of this study was to investigate the effects of short-pulse intestinal electrical stimulation (IES) on duodenal distention-induced delayed gastric emptying and vomiting in dogs and its possible mechanisms. The study was performed in 12 dogs with jejunal electrodes and a duodenal cannula in three separate experiments to investigate the effects of IES on duodenal distension (DD)-induced delayed gastric emptying and discomfort signs, vagal efferent activity, and jejunal tone. We found that: (i) IES signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 43 publications
(97 reference statements)
0
18
0
Order By: Relevance
“…From among the already mentioned applications in regenerative medicine, the concept of a "wireless" stimulation mediated by piezoelectric materials could find several applications in life sciences wherever electrical stimulation is needed, e.g., deep brain stimulation [99], gastric stimulation for gastroparesis [100], cardiac pacing for various cardiac arythmias [101], skeletal muscle stimulation in various neuropathies [102], etc.…”
Section: Discussionmentioning
confidence: 99%
“…From among the already mentioned applications in regenerative medicine, the concept of a "wireless" stimulation mediated by piezoelectric materials could find several applications in life sciences wherever electrical stimulation is needed, e.g., deep brain stimulation [99], gastric stimulation for gastroparesis [100], cardiac pacing for various cardiac arythmias [101], skeletal muscle stimulation in various neuropathies [102], etc.…”
Section: Discussionmentioning
confidence: 99%
“…A number of previous studies reported that duodenal nutrients or distension reduced proximal gastric tone, delayed gastric emptying, and increased pyloric contractions (17,32). Colon-rectal distension has been reported to induce delayed gastric emptying (20,31), abnormalities of gastric slow waves (1,21), and inhibition of proximal gastric tone (12).…”
Section: Effects Of Electrical Stimulation On Slow Waves and Optimal mentioning
confidence: 99%
“…Based on our knowledge, only dogs were used in prior GES studies and these investigations have two problems that limit interpretation. Firstly, they used non‐standard measures of emesis, often reporting a total ‘symptom score’ and not absolute, objectively quantifiable numbers of retches or vomits . The exception is one paper listing total emetic episodes; however, this report also has a potential confound by using repeated cisplatin chemotherapy injections in the same animals, with only the first test session as the control condition .…”
Section: Discussionmentioning
confidence: 99%
“…Although not specifically established for the vagus, it is known that cisplatin can produce peripheral neuropathy . The reported symptom scores were often combined with other measures, sometimes including licking tongue, closing eyes, yawning, belching, murmuring, rapid breathing, and defecating, and in other reports vomiting was scored 3 #bib4, or 5 if the symptoms occurred 1, 2, or 3 times and scored as ‘0’ if not present . We believe that these reports are largely not interpretable and difficult (if not impossible) to fit into the larger literature on emesis and evaluation of antiemetic therapies.…”
Section: Discussionmentioning
confidence: 99%